2018
DOI: 10.18632/oncotarget.24104
|View full text |Cite
|
Sign up to set email alerts
|

Tumor microenvironment promotes prostate cancer cell dissemination via the Akt/mTOR pathway

Abstract: Metastasis causes high mortality in various malignancies, including prostate cancer (PCa). Accumulating data has suggested that cancer cells spread from the primary tumor to distant sites at early stage, which is characterized by disseminated tumor cells (DTCs). However, lack of direct evidence of partial localized PCa cells occurring epithelial-to-mesenchymal transition (EMT) and disseminating to distant sites (e.g bone marrow). In this study, we used luciferase labeled PCa cells to establish an EMT mouse mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
1
9
0
1
Order By: Relevance
“…Despite these recent advances, treatments only provide scanty survival benefits and most patients develop disease relapse ( 183 ). Investigating on the mechanisms that may drive prostate cancer progression, different data reported that it is surrounded by a complex TME ( 184 , 185 ). In particular, MDSCs are the most renowned immune cells subset that has been reported to infiltrate the prostate TME ( 186 188 ).…”
Section: Mdscs In Prostate Cancermentioning
confidence: 99%
“…Despite these recent advances, treatments only provide scanty survival benefits and most patients develop disease relapse ( 183 ). Investigating on the mechanisms that may drive prostate cancer progression, different data reported that it is surrounded by a complex TME ( 184 , 185 ). In particular, MDSCs are the most renowned immune cells subset that has been reported to infiltrate the prostate TME ( 186 188 ).…”
Section: Mdscs In Prostate Cancermentioning
confidence: 99%
“…Thus, decreased uPAR expression leads to decreased integrin α 5 β 1 mediated adhesion to the ECM and reduced ERK activation, inducing a dormant state . Although it is not clear whether uPAR plays a role in tumor dormancy in the bone marrow, PC3 prostate cancer cells that were previously grown as subcutaneous tumors in vivo and were able to spontaneously disseminate to the bone marrow expressed elevated levels of uPAR protein by cytokine array in comparison to parental PC3 cells only grown in 2D culture, and uPAR was detected at a higher frequency in bone‐disseminated prostate cancer cells harvested from patients compared to tumor cells found in circulation and was associated with a poor Gleason score …”
Section: Factors Controlling Dormancy or Reactivationmentioning
confidence: 99%
“…Macrophages are of two different polarization types, including the ‘classically’ activated (M1) and the ‘alternatively’ activated (M2) types. Comito’s group reported that increasing infiltration of M2 macrophages was associated with worse pathological characteristics and poor prognosis of PCa [12], while Shi’s group showed that M2 macrophages increased proliferative, migratory and invasive abilities of PCa cells [13], hinting that M2 macrophages may play an important role in PCa progression. M2 macrophages could release some factors and enzymes, such as interleukin-6 (IL-6), interleukin-8 (IL-8), transforming growth factor-β (TGF-β), matrix metallopeptidase-2 (MMP-2), and matrix metallopeptidase-9 (MMP-9) to promote angiogenesis, tumourigenesis, and metastasis [14,15].…”
Section: Introductionmentioning
confidence: 99%